María Luisa Bombal: The Pen of the Angel (ALPHA. Journal of Arts, Literature and Philosophy, 1999)
I feel that the goblins take hold of time, and something of autumn brings a breeze of her memory to mind. It was an afternoon when I was invited by José Luis Gallardo. I arrived at what used to be María Luisa Bombal’s white house on Cinco Poniente in Viña del Mar. We climbed the stairs to the second floor, to the room that had been hers. Everything was there, just as she had left it before she departed. It seems that time stood still for a few minutes. Even a huge wardrobe of those old ones still held her most cherished memories, among which was a beautiful dress brought from France, that long black dress adorned with jet stones, which I would later wear for the portrayal of Brígida in the dramatization of the story “The Tree,” which took place at the Lyon Palace in Valparaíso.